2017
DOI: 10.1016/j.jvs.2016.12.063
|View full text |Cite
|
Sign up to set email alerts
|

Lombard Aorfix high angulation device, sac behavior following implantation

Abstract: In this study cohort, there is a low incidence of sac expansion with the Aorfix device. We were unable to demonstrate an association between neck length/angulation and sac expansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The evidence on a relationship between the preoperative AAA diameter and remodeling after EVAR varies greatly between different published studies—as shown in a recent review [ 13 ]. When focusing on studies reporting specifically on AAA remodeling one-year after EVAR, two studies found no correlation, while two others observed that a larger preoperative AAA diameter was related to an increased likelihood of AAA shrinkage [ 22 , 23 , 24 , 25 ]—consistent with the findings of this analysis. However, this observation might be distorted by the focus of this study, namely comparing shrinking with stable AAA after EVAR, consequently excluding growing AAAs.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The evidence on a relationship between the preoperative AAA diameter and remodeling after EVAR varies greatly between different published studies—as shown in a recent review [ 13 ]. When focusing on studies reporting specifically on AAA remodeling one-year after EVAR, two studies found no correlation, while two others observed that a larger preoperative AAA diameter was related to an increased likelihood of AAA shrinkage [ 22 , 23 , 24 , 25 ]—consistent with the findings of this analysis. However, this observation might be distorted by the focus of this study, namely comparing shrinking with stable AAA after EVAR, consequently excluding growing AAAs.…”
Section: Discussionsupporting
confidence: 82%
“…A recent systematic review demonstrated that two other studies that investigated AAA remodeling one-year after EVAR did not find significant relations between infrarenal angulation and AAA remodeling—in contrast to this study [ 13 ]. However, both studies were not comparable to this study as one study focused only on the Lombard Aorfix high angulation device and used another definition for neck angle [ 25 ], while the other study demonstrated smaller infrarenal angles with an undescribed measurement method of these angles [ 24 ].…”
Section: Discussionmentioning
confidence: 89%
“…For the grade of neck thrombus, mixed results were found. When scored as 1=mild and 3=severe, a higher thrombus grade was found to be significantly related to more sac enlargement at 4 years after EVAR (OR=0.11, 95%CI 0.02-0.76, p=0.02), which was not yet present at 1 year after EVAR 24 . Also, when the neck thrombus grade was expressed as the absolute degrees of neck thrombus circumference in a different population, a high degree was significantly more present in patients without AAA shrinkage (p=0.003) 19 .…”
Section: Anatomical Predictorsmentioning
confidence: 89%
“…The main findings of each study on the correlation of the anatomical parameter with AAA sac growth and shrinkage are presented in Table III [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] . A total of 27 anatomical parameters were Preoperative neck thrombus was indicated to predict less AAA sac shrinkage after EVAR 19,24,26,33 . The presence of this neck thrombus was found to be predictive of less AAA shrinkage at 6, 12, and 24 months after EVAR in two independent studies (p<0.05) 19,33 .…”
Section: Anatomical Predictorsmentioning
confidence: 99%
“…The Lombard Aorfix (Lombard Medical, Inc, Oxfordshire, United Kingdom) was developed to accommodate highly angulated aortic necks and was approved to treat proximal necks up to 90°. 9 , 10 The Anaconda endovascular graft (Vascutek, Terumo, Inchinnan, Scotland) was designed with hypothetic zero body columnar strength and high flexibility and the IFU advised for infrarenal angulation <90°. 11 Finally, the Medtronic Endurant endograft (Medtronic cardiovascular, Santa Rosa, Calif, USA) has been described to conform well to challenging anatomies, with IFU including infrarenal angle up to 75° with a neck length more than 15 mm.…”
Section: Discussionmentioning
confidence: 99%